2022
DOI: 10.1038/s41392-022-01123-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of eight SARS-CoV-2 variants rationally predicts immunogenicity clustering in sarbecoviruses

Abstract: A steep rise in Omicron reinfection cases suggests that this variant has increased immune evasion ability. To evaluate its antigenicity relationship with other variants, antisera from guinea pigs immunized with spike protein of SARS-CoV-2 variants of concern (VOCs) and variants of interest (VOIs) were cross-tested against pseudotyped variants. The neutralization activity against Omicron was markedly reduced when other VOCs or VOIs were used as immunogens, and Omicron (BA.1)-elicited sera did not efficiently ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Taken together, these studies demonstrate that RBD-based protein vaccines are immunogenic in humans. This supports our view that our uniquely formulated beta-variant RBD-Fc dimer/MF59® adjuvanted vaccine will work well as a heterologous booster subsequent to S-based vaccination in humans, particularly considering the increased breadth of immune responses that appear to be promoted by the beta variant 19,20,27,28 .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Taken together, these studies demonstrate that RBD-based protein vaccines are immunogenic in humans. This supports our view that our uniquely formulated beta-variant RBD-Fc dimer/MF59® adjuvanted vaccine will work well as a heterologous booster subsequent to S-based vaccination in humans, particularly considering the increased breadth of immune responses that appear to be promoted by the beta variant 19,20,27,28 .…”
Section: Discussionsupporting
confidence: 77%
“…While this is no longer a circulating VOC, having since been replaced by others and most recently omicron VOCs, our findings are that the beta RBD-hFc boost drives a broad nAb response that spans all of the SARS-CoV-2 VOCs we tested. Furthermore, studies with human samples have shown that exposure to the beta VOC was superior to the ancestral strain at driving broadly cross-reactive nAb, including those that can target omicron 19,20,27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis of genome-wide sequences, as well as amino acid sequences of the S-protein and RBD-domain, shows that the Omicron variant is genetically significantly removed both from the original SARS-CoV-2 variant and from all previous VOCs [2]. Moreover, a lot of studies confirm the weak cross-reactivity of the immune response formed to the variants of the virus from Alpha to Delta, in relation to the Omicron variant, as well as cross-reactivity in the opposite direction [3,4]. The Omicron variant shows sufficient genetic and structural distance from other SARS-CoV-2 variants, that suggests the possibility of separating the Omicron variant and its sub-lineages into a separate SARS-CoV-2 serotype [5].…”
Section: Introductionmentioning
confidence: 90%